Determination of lag acceptance and effects for left turning movements at intersections - Normalina Binti Zamberi (School of Environmental Engineering, University Malaysia Perlis, 2014)
The congestion of traffic flow at intersection occurs at peak hour. The movement of the vehicles is slow during the critical time of peak hour which can gives effect of delay time for the other movement of the vehicles in other direction intersections. In this researched, the methods used are manual traffic volume count and Sidra Intersection Version 5.1 software.